Prevalence of filaggrin loss‐of‐function variants in Chilean population with and without atopic dermatitis. (4th September 2021) - Cárdenas, Geovanna V.; Iturriaga, Carolina; Hernández, Caroll D.; Tejos‐Bravo, Macarena; Pérez‐Mateluna, Guillermo; Cabalin, Carolina; Urzúa, Marcela; Venegas‐Salas, Luis F.; Fraga, Juan P.; Rebolledo, Boris; Poli, Maria C.; Repetto, Gabriela M.; et al.
Abstract: Background: Filaggrin ( FLG ) loss‐of‐function variants are major genetic risk factors for atopic dermatitis (AD), but these have not been studied in Latin American populations with and without AD. Methods: FLG variants R501X and 2282del4 were genotyped in 275 Chilean adults with and without AD from the "Early origins of allergy and asthma" (ARIES) cohort and in 227 patients from an AD cohort based in Santiago, Chile. Results: Among adults in the ARIES cohort, 3.3% were carriers of R501X and 2.9% of 2282del4 variants, all heterozygotes. In this cohort, 6.2% were FLG variant carriers: 11.1% of subjects reporting AD were carriers of FLG variants vs. 5.2% in those without AD ( P  = 0.13). In this first cohort, FLG variants were not significantly associated with asthma, allergic rhinitis, or food allergy. In the AD cohort, the prevalence of FLG variants was 7% for R501X, 2.2% for the 2282del4 variant, and 9.3% for the combined genotype. In this cohort, FLG variants were present in 15.5% of severe AD vs. 7.1% of mild‐to‐moderate AD subjects ( P  = 0.056). Evaluation of Chilean population from both cohorts combined (n = 502) revealed that FLG variants were not significantly associated with AD (OR = 1.92 [95% CI 0.95–3.9], P  = 0.067) but were associated with asthma (OR = 2.16 [95% CI 1.02–4.56], P  = 0.039). Conclusions: This is the first study to evaluate FLG loss‐of‐function variants R501X and 2282del4 in Latin American population, revealing a similar prevalence of these FLG variant carriers to that of European populations. Among Chileans, FLG variants were significantly associated with asthma but not AD.